Contrast enhanced magnetic resonance imaging of the terminal ileum in children with Crohn’s disease - Laghi, A (Copyright 2003 by Gut, 2003)
Background and aims: Recently, magnetic resonance imaging (MRI) has been introduced in the diagnosis of patients with inflammatory bowel disease (IBD). However, it is still rarely reported in paediatric IBD. We studied the diagnostic value of gadolinium enhanced MRI in revealing inflammation of the distal ileum in children with Crohn’s disease (CD) and in differentiating them from patients with other inflammatory diseases of the gut. MRI was performed using a polyethylene glycol (PEG) solution as oral contrast agent to distend the small bowel (CE-PEG-MRI). Subjects and methods: Seventy five consecutive patients (median age 13.6 years, range 8–17) with suspected CD underwent ileocolonoscopy with biopsy and CE-PEG-MRI. CD activity was measured by the paediatric Crohn’s disease activity index (PCDAI). CE-PEG-MRI was evaluated with an overall score calculated, taking into account both wall thickness and contrast enhancement. Results: Active CD with distal ileitis was diagnosed in 26 cases, active ulcerative colitis (UC) in 18, and spondyloarthropathy and indeterminate ileocolitis in 11; 20 children served as controls. In all CD patients, CE-PEG-MRI revealed a marked ileal involvement with increased wall thickness and parietal contrast enhancement and showed a high concordance with endoscopy and histology, whereas the test was negative in all controls. Of the 18 UC patients, CE-PEG-MRI was negative in 15 and showed a mild parietal contrast enhancement of the terminal ileum in only three of seven patients with backwash ileitis. Among the group of spondyloarthropathy patients, six had mucosal erosions and five mild superficial ileitis: CE-PEG-MRI was negative in four and revealed only mild parietal contrast enhancement of the ileal wall in seven. CE-PEG-MRI did not show an increase in wall thickness of the distal ileum in any of the UC or spondyloarthropathy patients. The sensitivity and specificity of CE-PEG-MRI related to the presence of erosive ileitis, as documented by endoscopy, were 84% and 100%, respectively. In addition, the test correlated markedly with endoscopy and histology in the entire population (r=0.94; r=0.95, respectively) as well as with the PCDAI in CD patients (r=0.91). Conclusions: In children with active CD, CE-PEG-MRI is a very sensitive and specific test for the detection of distal ileitis and for differentiation from other inflammatory diseases of the gut. The test could also be useful for the firstline diagnostic approach in children with suspected CD. The high correlation of CE-PEG-MRI with ileal endoscopy and histology as well as with PCDAI makes this test of great interest for future studies as a tool for monitoring the clinical course and the effect of therapy in CD patients.